Molecular Identification of Lactic Acid Bacteria from Broiler Chicken Meat - Mudawaroch, Roisu Eny; Setiyono, Setiyono; Yusiati, Lies Mira; Suryanto, Edi (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2023)
Lactic acid bacteria are bacteria used to ferment food. Molecular identification of isolates of lactic acid bacteria has a high degree of accuracy compared to morphological identification. This study aimed to molecularly identify isolates of lactic acid bacteria from broiler chickens. Molecular identification is carried out in 3 stages, namely: rRNA gene amplification stage, squencing and phylogeny tree. PCR electrophoresis results obtained amplicone results measuring about 1,500 bp. The results of BLAST analysis showed that the gen 16S rRNA sequence of BR 17 lactic acid bacteria isolate had a 97-98% similarity with the genome sequence of the Lactobacillus fermentum strain. Development of phylogenetic tree isolates of single clusters of lactic acid bacteria BR 17 with strains of Lactobacillus fermentum CAU2036, Lactobacillus fermentum JCM 7772, and Lactobacillus fermentum 10-18. The identification results of lactic acid bacteria isolate BR 17 showed Lactobacillus fermentum BR 17.